In situ X‐ray crystallographic study of the structural evolution of colloidal crystals upon heating. (23rd June 2013) - Zozulya, A. V.; Meijer, J.‐M.; Shabalin, A.; Ricci, A.; Westermeier, F.; Kurta, R. P.; Lorenz, U.; Singer, A.; Yefanov, O.; Petukhov, A. V.; Sprung, M.; Vartanyants, I. A.
<x xml:space="preserve">Abstract</x> The structural evolution of colloidal crystals made of polystyrene hard spheres has been studied in situ upon incremental heating of a crystal in a temperature range below and above the glass transition temperature of polystyrene. Thin films of colloidal crystals having different particle sizes were studied in transmission geometry using a high‐resolution small‐angle X‐ray scattering setup at the P10 Coherence Beamline of the PETRA III synchrotron facility. The transformation of colloidal crystals to a melted state has been observed in a narrow temperature interval of less than 10 K.